A Review of Acupuncture Treatment for Post-Stroke Hiccup - Chen, Honglu; Zhang, Yi; Ren, Keming (Journal of Contemporary Medical Practice, 2026)
Post-stroke hiccup (PSH) is a common complication following stroke, caused by paroxysmal spasm of the diaphragm. Persistent episodes can lead to nutritional intake disorders, electrolyte imbalances, and may even exacerbate brain injury. Acupuncture therapy offers advantages of rapid onset and high safety in treating PSH by regulating central nervous system excitability and inhibiting diaphragmatic spasm. This study reviewed literature from databases including CNKI, Wanfang, and PubMed from 2015 to 2025, identifying nine frequently used acupuncture therapies (such as conventional body acupuncture, electroacupuncture, eye acupuncture, etc.). The core mechanism is considered to be calming the ascending counterflow, harmonizing the stomach, and regulating qi movement, demonstrating significant efficacy in improving patients’ quality of life.